La yuca en la economia de America Latina - Cock, James H.; Lynam, John K. (International Center for Tropical Agriculture, 1991)
Some of the actual and potential markets for cassava in tropical Latin America are discussed. Data are presented for Brazil (the world's largest cassava producer), Paraguay (the Latin American country with the highest per capita cassava production), the Andean countries, Central America, and the Caribbean. An analysis of government policies in South America as a whole in the 1980s indicates reduced subsidies to products that compete with cassava, thus enhancing the competitive ability of the crop. Expansive markets are seen for fresh conserved cassava for human consumption, dried cassava for animal feed, and high-quality CF for human consumption. In Mesoamerica, cassava has the potential to compete in animal feed markets, but, in general, lack of institutional support for the crop hinders the development of a dried cassava industry. In the Caribbean, with the exception of Cuba, Haiti, and the Dominican Republic, cassava is unlikely to have a significant role in the agricultural economy. In Cuba and the Dominican Republic, as the demand for fresh cassava is satisfied, an increasing proportion of production will move into animal feed markets. (CIAT)